2014
DOI: 10.1093/mmy/myu038
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled corticosteroids and Aspergillus fumigatus isolation in cystic fibrosis

Abstract: Aspergillus fumigatus isolation in cultures from respiratory specimens of patients with cystic fibrosis (CF) is quite common; however, the role of A. fumigatus as a pathogen and whether its presence is associated with progression of pulmonary disease remain unclear. We investigated the association between inhaled corticosteroids and the recovery of A. fumigatus by performing a retrospective cohort study of CF patients born between 1988 and 1996. The patients' medical records from their first visit to the CF Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 37 publications
2
28
0
Order By: Relevance
“…In accordance with Noni et al, who reported a possible link between inhaled corticosteroids and ABPA, we found significantly more patients on inhaled corticosteroids in the pre‐index period for the ABPA group; therefore, immunomodulation favoring Af colonization could be involved. Although wheezing as an early sign of ABPA could have induced the use of inhaled corticosteroids, the higher use during the pre‐index years favors a possible immunologic link.…”
Section: Discussionsupporting
confidence: 91%
“…In accordance with Noni et al, who reported a possible link between inhaled corticosteroids and ABPA, we found significantly more patients on inhaled corticosteroids in the pre‐index period for the ABPA group; therefore, immunomodulation favoring Af colonization could be involved. Although wheezing as an early sign of ABPA could have induced the use of inhaled corticosteroids, the higher use during the pre‐index years favors a possible immunologic link.…”
Section: Discussionsupporting
confidence: 91%
“…fumigatus struggles and may help explain why A. fumigatus appears in CF airways later in the course of the disease (5,6,9,10,13,14,16). Evolution of P. aeruginosa may act in concert with other factors favoring A. fumigatus colonization, including repeated antibacterial courses and inhaled corticosteroids (76).…”
Section: Discussionmentioning
confidence: 99%
“…Other than underlying pulmonary condition by itself, undergoing treatments, particularly ICS, which was used in our PE group might also promote Aspergillus colonization in the airways. ICS increased the rate of isolation and sensitization of Aspergillus in COPD [17] and cystic fibrosis [18] and high dose prescription was a risk of IPA [19,20], ICS may increase Aspergillus loads in the lung tissue and contribute to more invasive and subacute clinical courses like bacterial pneumonia.…”
Section: Discussionmentioning
confidence: 99%